FACTORS INFLUENCING STUDENT’S MENTAL HEALTH IN UNIVERSITI TEKNOLOGI MARA KELANTAN - Nur Wahidatun Najihah Binti Mohd Zahidi,; Siti Nur Zahirah Omar,; Nur Nadhira Husna Binti Jafri,; Nor Hafidatul Najwa Binti Mohd Nazman,; Nur Syahirah Binti Nawawee, (Journal of Islamic, Social, Economics and Development, 2024)
This research is to undertake a comprehensive and nuanced investigation into the complex interplay of factors that contribute to the student’s mental health of UiTM Kelantan. The mental well-being of students in a higher education context is paramount, given its implications for their academic success, personal development, and overall quality of life. This study seeks to delve deeply into several pivotal factors, encompassing environmental determinants, the consequences of protracted financial problems, the multifaceted influence of academic pressures, and the enduring impact of family dynamics. Each of these elements holds a critical place in shaping the mental health landscape of UiTM Kelantan Branch students. A comprehensive understanding of these intricate relationships is essential for developing effective interventions and robust support systems, fostering resilience and well-being in this unique student population.